Flexibilidade no desenvolvimento de software: a percepção de gerentes de projeto em Aracaju-SE - Lima, Michell Angelo Santos (2013)
Managers of software development projects increasingly need to deal with factors such as competition, demand for quality, shorter product life cycles and constant technological changes in the market. Thus, it was realized that flexibility is a critical issue for software development projects, since it is necessary to improve the ability of responses to market changes, so that there are few reworks, minimized costs, responsiveness and capacity innovation. Aiming to contribute to this discussion, this study sought to investigate how the characteristics of flexibility are perceived by project managers in software development. The theoretical framework of the processes of software development Cockburn (2001), Abrahamsson et al. (2003), Vinekar (2006) and Laudon and Laudon (2010) were the basis for this study. The methodology has a descriptive and qualitative and adopted the search strategy multiple case study in which the cases are characterized by the processes of software development, and as a source of evidence, chose to project managers who work in Aracaju, considering that these professionals have a broader view of the development process. As results, in treating of flexibility with respect to the customer, all respondents stated that customer participation in the development process is important for the proper performance of the project as possible to anticipate potential changes. Regarding flexibility in the working group, four of the five managers interviewed said that team members do not react well to changes in the project, and that there is an effort in most projects to negotiate with the client possible changes in cost and time. Regarding the process flexibility, the five respondents agree on the advantages of a good definition of the processes within the organization. However, all processes are capable of adapting to achieve the required results. The findings in this study therefore demonstrate that the project managers, while focusing on the technical aspects of the software development process, associate to the level of success of the project to other factors, such as flexibility in the process, working groups and with respect to the customer.